The Determinants of the Attractiveness of an Industry: An Extension of the Porter’s Five-Forces Framework (Global Journal of Management and Business Research, 2022)
In this paper I review and provide a more extensive theoretical grounding for Porter s five- forces model for the determination of the attractiveness of an industry I argue that the model is incomplete given its implicit assumptions about a firm s financing activities in implementing its competitive strategy It is my opinion that an absolute paradigm for the determination of the attractiveness of an industry must take into consideration the industry s optimal capital structure as well as the tendency for the power of providers of debt capital to vary across industries and to be crucial in the formation of industry profitability
Keywords: industry attractiveness; competitive forces; optimal industry capital structure; power of lenders